An augmented lecture feedback system to support learner and teacher communication. (4th June 2013) - Zarraonandia, Telmo; Aedo, Ignacio; Díaz, Paloma; Montero, Alvaro
Abstract In this paper, it is advocated that the feedback loop between learners and teachers could be improved by making use of augmented reality (AR) techniques. The bidirectional communication between teacher and learners is sometimes hampered by students' fear of showing themselves up in front of their classmates. In order to overcome this problem, a system is proposed whereby teachers receive immediate and private feedback both individualised for each student as well as aggregated for the whole class. With that purpose, the teacher, who is equipped with a head‐mounted AR display, can visualise symbols that represent the status students have stated using private devices in relation to the lecture content. In order to explore the possibilities of this approach, an experience was conducted in a lecture on a university course. The results are encouraging and suggest that as this technology matures and less intrusive AR display models become available, it could provide effective support to improve communication and interaction during lectures. A video abstract of this article can be viewed at http://www.youtube.com/watch?v=qUCkNkuAiK8